Financial Literacy and Participation in Derivative Market in Kathmandu Valley (Quest Journal of Management and Social Sciences, 2026)
Background: Financial literacy is critical for informed investment decisions and effective participation in financial markets. Investors with higher literacy better understand complex instruments, such as derivatives, manage risk, and optimize returns. In emerging markets like Nepal, awareness, access, and socioeconomic factors further influence investor participation.Purpose: This study examines financial market involvement from the perspectives of financial literacy, awareness, risk aversion, and participation costs, focusing on derivatives markets.Design/methodology /approach: Grounded in Expected Utility Theory, the study uses an explanatory research design to explore the relationship between financial literacy and derivatives market participation. A non-probability convenience sampling method yielded 297 respondents, with data collected via structured questionnaires through KOBO Toolbox. Ordered logistic regression in STATA was employed to analyze the impact of financial literacy on participation.Findings: Financial literacy positively affects derivatives market participation. Key factors influencing participation include gender, various information sources (financial institutions, school, handouts), purchase installments, and interest coverage.Conclusion: Men, married individuals, and financially literate investors are more likely to participate in derivatives markets. Participation is also shaped by risk attitude and income levels. Policy measures enhancing financial literacy and market awareness can stimulate financial market engagement, increase trading, and boost economic activity. Investors should understand derivatives before investing and diversify holdings to maximize returns while minimizing risk.Keywords: Investment decision, derivative market, financial literacy, expected utility theory, ordered logistic model.